APPLICATION OF THE OUTDOOR STUDY METHOD TO IMPROVE SOCIAL SKILLS AND UNDERSTANDING OF THE CONCEPT OF NUTRITIONAL SUBJECTS - Dian Puspita Anggraini (JOSAR (Journal of Students Academic Research), 2022)
This study aims to determine efforts to improve process skills and understanding of the concept of nutrition science courses using the Outdoor Study method, as well as improving process skills and understanding of nutrition science concepts using the Outdoor Study method. This type of research is CAR (Classroom Action Research) model of Kemmis and Taggart whose steps consist of planning, implementing and observing, reflecting. Data collection techniques using observation, questionnaires, interviews, concept understanding tests and documentation. The data analysis technique used qualitative analysis. The research subjects were students of the fifth semester of the Biology Education study program at the Islamic University of Balitar, Blitar. The results showed that the increase in learning social skills and understanding of the concept of Nutrition Science was shown from the observations of learning social skills in the first cycle of 67.78%, increasing to 78.89% in the second cycle. The results of the learning social skills questionnaire in the first cycle were 71.46%, increasing to 77.40% in the second cycle. The average result of the percentage of social skills in the first cycle was 69.62% and 78.14% in the second cycle. The results of the assessment to determine the understanding of the concept, namely the post-test results in the first cycle obtained an average value of 74.33 with 21 students (70%) completed and 9 students (30%) incomplete. Cycle II obtained an average grade of 79.83 with 25 students (83.33%) completed and 5 students (16.67%) incomplete.